2022
DOI: 10.3389/fmed.2022.906403
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and MicroRNA-Gut Microbiota Regulatory Mechanisms of Acupuncture for Severe Chronic Constipation: Study Protocol for a Randomized Controlled Trial

Abstract: BackgroundSevere chronic constipation (SCC) is a common functional gastrointestinal (GI) disorder associated with disruptions in GI motility. Abnormalities between gut microbiota and microRNAs (miRNAs) are implicated in the pathogenesis of GI motility in SCC. Acupuncture has been shown to improve constipation-related symptoms and rebalance the gut microbiota. This protocol proposed a plan to explore the hypothesis that the efficacy of acupuncture is associated with the crosstalk between gut microbes and miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Currently, laxatives are a favorable choice for alleviating relative symptoms of FC (Liu et al, 2016 ). However, frequent usage of laxatives can result in drug dependence and a cathartic colon; therefore, a laxative is not a satisfactory therapy for FC patients (Yao et al, 2022 ). Therefore, there is a perceived need to perform further research into the mechanism of FC, with the aim of enhancing the efficacy of treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, laxatives are a favorable choice for alleviating relative symptoms of FC (Liu et al, 2016 ). However, frequent usage of laxatives can result in drug dependence and a cathartic colon; therefore, a laxative is not a satisfactory therapy for FC patients (Yao et al, 2022 ). Therefore, there is a perceived need to perform further research into the mechanism of FC, with the aim of enhancing the efficacy of treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing number of randomized clinical trial (36,60,61) have recruited healthy volunteers and determined the pathological features in the population of patients by comparing them with patients. Patients with MCI were reported to have altered levels of peripheral and cerebrospinal fluid inflammatory markers, abnormal cognitive-related brain network function, and distinct gut microbiota composition compared with healthy controls (62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the primary physiopathologic mechanism of FC is decreased intestinal motility associated with reduced sensitivity of both sympathetic and parasympathetic nervous systems. Previous studies have demonstrated that acupuncture at acupoints ST25, ST37, and SP14 can effectively increase bowel movements (Liu et al, 2016;Yao et al, 2022b). It has been described that the deep sections of ST25 and SP14 correspond to the nerve segments of the large intestine (T10) and the small intestine (T11), respecitevely, which exert bidirectional influence on peristalsis and contraction via sympathetic or parasympathetic nerves (Yu et al, 2016;Zeng and Chen, 2022).…”
Section: Discussionmentioning
confidence: 99%